The Study of the Relationship between Social-Cultural Factors with Attitudes toward Haqqu N-Nas (The Right of Men) (Case Study: Youth 18-29 Years Old in Shiraz) - majid movahed; mandana karimi (توسعه اجتماعی, 2016)
This study aims to The Study of the Relationship between Social-Cultural Factors with Attitudes toward Haqqu n-nas (The right of men): a Case Study of The Shiraz Youth 18-29 years old. In this way, first of all the topic of study was introduced and analyzed. The conducted research by other scientists in tow part, internal and foreign researches, and then existing theories in the field of study were analyzed. The theories of Max Weber were elected as theoretical framework. The method of this study was quantitative survey with questionnaire. 600 youth (18-29 ages) in Shiraz city by multistage sampling were elected and were analyzed. The gathered data were analyzed by SPSS software. The results in descriptive and inferential parts were presented and research hypotheses were analyzed. Among 12 hypotheses in the study, only 4 hypotheses were verified. Multivariate regression has shown that rate of religiosity, age, ethnic and Residence Variables have explained 21/6 percent of the variations of dependent variable (Attitudes toward Haqqu N-Nas). At the end obtained results have discussed.